SPEECH AND INTELLECTUAL DEVELOPMENT OF STUDENTS - Barno Tajimovna Badalova (Galaxy International Interdisciplinary Research Journal, 2022)
The article reveals aspects of teaching the Russian language at school at the present stage, the formation of students’ linguistic, cultural and communicative competence.